CGAMP inhibits tumor growth in colorectal cancer metastasis through the STING/STAT3 axis in a zebrafish xenograft model. Issue 95 (December 2019) - Jiang, Xiaofeng; Liu, Guangping; Hu, Zhiyi; Chen, Guiqian; Chen, Jianqing; Lv, Zhengbing
Abstract: The leading cause of mortality due to colorectal cancer (CRC) is highly associated with the development of liver metastases. Recently, we described cGAMP that is closely related to the metastatic state wherein the progress of metastatic tumors is associated with favorable outcomes in a zebrafish xenograft model. cGAMP was administered and the expression levels of type-I interferons were induced amongst tumor tissues to illuminate the overall measure of the induced STING/STAT3 axis in colorectal liver metastases. Furthermore, cGAMP–STING dependent STAT3 activation resulted in the inhibition of tumor cell proliferation, viability, and invasion in vitro. The subtotal reduction in tumor growth attributed to a large number of infiltrating inflammatory cells in vivo. We showed that cGAMP inhibited migration through angiogenesis by up-regulating IL-2, TNF-α, and IFN-γ, whereas STAT3 down-regulation inhibited CXCL8, BCL-2, and VEGFA expression. The importance of cGAMP in inhibiting the invasion front of CRC confirmed that the cGAMP dependent activation of STING/STAT3 axis played a key role in the inhibition of tumor progression. Highlights: This is the first discovery that the STING/STAT3 signal axis plays an important role in CRC proliferation and metastasis. Zenrafish is a potential model for evaluating cancer metastasis. The STING/STAT3 signal axis is necessary for the activation of antitumor immunity in a zebrafish tumor xenograft model.